2006
DOI: 10.1093/molehr/gal013
|View full text |Cite
|
Sign up to set email alerts
|

Maternal smoking during pregnancy and genetic polymorphisms in the Ah receptor, CYP1A1 and GSTM1 affect infant birth size in Japanese subjects

Abstract: Genetic susceptibility to tobacco smoke might have relation to adverse pregnancy outcomes. To estimate the effects of maternal smoking and genetic polymorphisms on infant birth weight and length, we conducted a prospective cohort study of 293 women who delivered singleton live births in Sapporo, Japan. Birth weight and length were significantly lower among infants born to continuously smoking women having the aryl hydrocarbon receptor (AhR) wild type genotype (Arg/Arg; 211 g +/- 76 g; 1.2 cm +/- 0.4 cm, p < 0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
59
2
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(64 citation statements)
references
References 40 publications
1
59
2
2
Order By: Relevance
“…A possible reason for the lack of a −634C/G genotype effect on CRP concentrations in current smokers is that continuous smoking, which stimulates inflammation, could reduce the −634G allele's effect on CRP concentration; the −634G allele may increase CRP concentration when smoking does not stimulate inflammation. Also, glutathione S-transferase (GST) M1 and P1, phase II detoxification enzymes, were related to increased risk of smokingrelated diseases (29,30) and to the metabolism of many carcinogenic compounds in tobacco smoke (31). It has been reported that the GSTM1 and GSTP1 gene polymorphisms are related to inflammation (32).…”
Section: -24)mentioning
confidence: 99%
“…A possible reason for the lack of a −634C/G genotype effect on CRP concentrations in current smokers is that continuous smoking, which stimulates inflammation, could reduce the −634G allele's effect on CRP concentration; the −634G allele may increase CRP concentration when smoking does not stimulate inflammation. Also, glutathione S-transferase (GST) M1 and P1, phase II detoxification enzymes, were related to increased risk of smokingrelated diseases (29,30) and to the metabolism of many carcinogenic compounds in tobacco smoke (31). It has been reported that the GSTM1 and GSTP1 gene polymorphisms are related to inflammation (32).…”
Section: -24)mentioning
confidence: 99%
“…Interestingly, variants of enzymes regulated by AHR activity (CYP1A1 m1/m2 + m2/m2) or linvolved in PAH elimination (GSTM1 -1-) sensitized fetuses to the effects of maternal smoking (Sasaki et al, 2006). This study directly links PAH exposure to deficits in AHR signaling in the context of fetal programming.…”
Section: Thy11 Merged Discussionmentioning
confidence: 75%
“…Relevant to our studies is that expression of AHR protein with af!~/arg at codon 211 sinnificantly lowered birth weight and length in offspring exposed to in utero tobacco smoke (Sasaki et a/., 2006). Interestingly, variants of enzymes regulated by AHR activity (CYP1Al m1/m2 + m2/m2) or involved in PAH elimination (GSTM1 -/-) sensitized fetuses to the effects of maternal smokin!~ (Sasaki et al, 2006). This study directly links PAH exposure to deficits in AHR signaling in the context of fetal pronramming.…”
Section: Introductionmentioning
confidence: 67%
See 2 more Smart Citations